Stereotactic body radiotherapy in patients with lung tumors composed of mainly ground-glass opacity. (26th March 2020) - Onishi, Hiroshi; Shioyama, Yoshiyuki; Matsumoto, Yasuo; Shibamoto, Yuta; Miyakawa, Akifumi; Suzuki, Gen; Nishimura, Yasumasa; Sasaki, Ryohei; Miyawaki, Daisuke; Kuriyama, Kengo; Komiyama, Takafumi; Marino, Kan; et al.
Abstract: We retrospectively reviewed the effect of stereotactic body radiation therapy (SBRT) in patients with stage I lung cancer whose lung tumor showed a nodular appearance of ground glass opacity, so-called ground glass nodule (GGN). A total of 84 patients (42 men, 42 women; mean age, 75 years) with stage I lung cancer with GGN accompanying a solid component <50% in diameter of the tumor and no metastases were studied. Concerning histology, 32 tumors were adenocarcinoma, 1 was squamous cell carcinoma, 2 were unclassified carcinoma and 49 cases were histology-unproven but increased in size or had a positive finding in 18 F-FDG positron emission tomography (PET) examination. The median tumor size was 20 mm (range, 10–41 mm). All of the patients were treated with SBRT, and the total prescribed dose at the isocenter ranged between 48 Gy in four fractions and 84 Gy in ten fractions. Median follow-up duration was 33 months. No patient had local failure nor regional lymph node failure. The 3-year rate of distant failure was 2.6%. Two patients who experienced distant metastases had a past surgical history of initial lung cancer before SBRT. The rates of cause-specific and overall survival at 3 years were 98.2 and 94.6%, respectively. Treatment-related adverse events of ≥grade 4 were not reported. Although more cases and longer follow-ups are mandatory, SBRT may be one of the radical treatment options for patients with GGN.